A novel energy efficient path for nitrogen fixation using a non-thermal arc. Issue 21 (1st April 2021) - Muzammil, Iqbal; Lee, Dae Hoon; Dinh, Duy Khoe; Kang, Hongjae; Roh, Seon Ah; Kim, You-Na; Choi, Seongil; Jung, Chanmi; Song, Young-Hoon
Abstract : The studied process offers high NO selectivity with low energy consumption, which is much lower than the previously reported value of plasma-assisted atmospheric nitrogen fixation and is close to that of the Haber–Bosch process. Abstract : Plasma-assisted nitrogen fixation is a promising sustainable and clean alternative to the classical Haber–Bosch process. However, the high energy consumption and low production rate of plasma-assisted nitrogen fixation limit its application. This study shows that the non-thermal (non-equilibrium) enhancement of the arc plasma significantly reduces the energy consumption of nitrogen fixation. The highest energy efficiency with high NO selectivity is observed with a low specific energy input (SEI). However, the highest production rate is reached at a high SEI. The studied process offers high NO selectivity (up to 95%) with low energy consumption (∼48 GJ per tN) at 0.1 kJ L −1 SEI, which is much lower than the previously reported value of plasma-assisted atmospheric nitrogen fixation and is close to that of the Haber–Bosch process.